Pleurodesis - Lamb, Carla; Li, Andrew; Thakkar, Dhaval; Lee, Pyng (Seminars in Respiratory and Critical Care Medicine, 2019)
Symptomatic pleural disease, specifically malignant pleural effusion, refractory benign pleural effusion, and pneumothoraces are common diseases that often require therapeutic interventions. The spectrum of management strategies often includes selection of a chemical pleurodesis agent administered in combination with an indwelling pleural catheter or chest tube.Additionally, there is a role for minimally invasive techniques which include medical thoracoscopy or more advanced video-assisted thoracoscopic approaches. Ongoing clinical trials continue to evolve best practices regarding the optimal sclerosant agents and procedural approaches in the management of these diseases.
Keywords: pleural effusion; malignant pleural effusion; pneumothorax; pleurodesis; talc; indwelling pleural catheter; chest tube; medical thoracoscopy; video-assisted thoracoscopic surgery